Analisis Mutu Organoleptik dan Kadar Air Ikan Roa (Hemiramphus sp.) Asap dengan Metode Pengasapan Berbeda - Rosdiani Azis; Ingka Rizkyani Akolo (Institut Pertanian Bogor, 2020)
Fish is one source of high protein and included a commodity which is easily to decay. The way to inhibit the decay process of fish is fumigation. One of the smoked fishes that is often consumed by Gorontalo people is smoked Roa fish (Hemiramphus sp.). Smoked Roa fish is processed with traditional way through burning using woods as the fuel. Simply or conventionally fish processing like that has several flaws such as less protected of the sanitation aspects in the processing protocol. In order to improve the traditional processed product of Gorontalo, that is a smoked Roa fish, a new breakthrough in making smoked Roa fish was made by using the liquid smoke method. Liquid smoke contains compound of phenol and organic acids that are antibacterial and antioxidant compounds. The purpose of this research is to evaluate the effect of using different fumigation methods on organoleptic quality (appearance, smell, taste, and texture) of smoked Roa fish. The fumigation methods used were fumigation with liquid smoke and fumigation with traditional method. This research used a completely randomized design with 2 treatments and 3 times of replications. The results showed that liquid smoked Roa fish were preferred by panelists, compared to traditional smoked Roa fish. Liquid smoked Roa fish had a bright appearance, the smoke color was spread evenly (uniform), the smell of soft smoke, delicious fish taste, and hard texture that were different from traditional smoked Roa fish which appearance tended to be dull, the color of the smoke was not evenly distributed, the smoke taste in the fish was also quite sharp. Liquid smoked Roa fish also had a lower water content than traditional smoked Roa fish. Statistical tests showed that the fumigation method had a significant effect on the smell and water content of smoked Roa fish. Keywords: hedonics, liquid smoke, organoleptic, Roa fish, traditional fumigation